STRATEGI LINTAS SEKTORAL UNTUK PENGUATAN KESEHATAN PADA CALON PENGANTIN - Eka Vicky Yulivantina; Siswanto Pabidang; Gunarmi (WOMB Midwifery Journal, 2022)
Maternal and infant mortality rates are caused by complications in pregnancy and childbirth as a result of no good pregnancy planning. Limited information on prospective brides causes low awareness of the importance of premarital health services. This is directly proportional to low participation in accessing health services. The purpose of this study is to determine cross-sectoral strategies for strengthening health for prospective brides in the city of Yogyakarta. This research method is qualitative with a phenomenological study approach, namely exploring subjective experiences from the perspective of research informants. Determination of informants is done using purposive sampling technique, namely the determination of informants based on certain goals and criteria that have been set. Data collection was carried out by in-depth interviews with informants. The validity of the data was tested by testing credibility, transferability, dependability and confirmability by extending the observation period, increasing persistence, peer debriefing, member check and triangulation until the data collected was saturated for four months. Data analysis was carried out using the van meter and van horn theoretical approaches. The conclusion in this study is that health services for the prospective premarital couple aim to prepare the health of the prospective premarital couple for pregnancy, childbirth and contraceptive preparation; Human resources involved in the service are KUA officers, BP4 officers, midwives, lab officers, general practitioners, nutrition officers and psychologists; All KUA, BP4 and health workers serve wholeheartedly regardless of the background of the bride and groom; Communication between organizations is mainly carried out through SOPs for premarital couple services and support from the environment, economy, social, and politics in the form of cross-sectoral support from KUA and BP4, the Yogyakarta City area is not a conflict area, so it does not affect the stability of services for the premarital couple.